Advances in applying of multi-omics approaches in the research of systemic lupus erythematosus: Summarization of biomarkers from different omics, and discussion of challenges and advances in integrative analysis of multi-omics in SLE studies. (3rd July 2020) - Song, Wencong; Tang, Donge; Chen, Deheng; Zheng, Fengping; Huang, Shaoying; Xu, Yong; Yu, Haiyan; He, Jingquan; Hong, Xiaoping; Yin, Lianghong; Liu, Dongzhou; Dai, Weier; et al.
Abstract: Systemic lupus erythematosus (SLE), an autoimmune disease that causes multiorgan injury, has an unclear etiology and complex pathogenesis. Numerous studies have found abnormal alterations in mRNAs, proteins and/or metabolites in SLE patients. These findings have extended our understanding of the pathogenesis of SLE. Novel omics techniques, such as transcriptome, proteome and metabolome profiling, can identify and quantify large numbers of biomarkers of human diseases. However, in most cases, biological reactions are the consequences of interactions among genes, proteomes, and metabolites. Single biomolecules or signaling pathways cannot fully explain biological traits or functions. Therefore, integrative multi-omics analysis can help us systematically comprehend the intrinsic molecular mechanisms underlying biological function and pathogenesis. Integrating transcriptome, proteome, and metabolome KEGG enrichment analysis data will expand our knowledge of the pathogenesis of SLE. This review discusses the application, research progress and outlook on integrative multi-omics analysis in SLE research.